2021
DOI: 10.1530/ec-21-0411
|View full text |Cite
|
Sign up to set email alerts
|

Sodium alterations impair the prognosis of hospitalized patients with COVID-19 pneumonia

Abstract: Objective: Dysnatremia is common in hospitalized patients, often worsening the prognosis in pneumopathies and critical illnesses. Information on COVID-19-related hyponatremia is partially conflicting, whereas data on hypernatremia in this context are scarce. We assessed, in a cohort of COVID-19 inpatients: the prevalence of sodium alterations at admission and throughout their hospitalization; their association with inflammation/organ damage indexes; their short-term prognostic impact. Study design and methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 39 publications
5
19
1
1
Order By: Relevance
“…[34,41,42] On the contrary, admission hypernatraemia or the development of hypernatraemia during hospitalisation have been associated with increased mortality and death. [30,35,36,39,40] Similarly, we found a correlation between hypernatraemia and a long hospital stay. It has been reported that SARS-CoV-2 binds to the angiotensin-converting enzyme 2 receptor in kidney tubules.…”
Section: In Practicesupporting
confidence: 73%
See 1 more Smart Citation
“…[34,41,42] On the contrary, admission hypernatraemia or the development of hypernatraemia during hospitalisation have been associated with increased mortality and death. [30,35,36,39,40] Similarly, we found a correlation between hypernatraemia and a long hospital stay. It has been reported that SARS-CoV-2 binds to the angiotensin-converting enzyme 2 receptor in kidney tubules.…”
Section: In Practicesupporting
confidence: 73%
“…Dysnatraemia in COVID-19 hospitalised patients has generally been associated with poorer outcomes. [30][31][32][33][34][35][36][37][38][39][40][41][42] Both hypernatraemia and hyponatraemia, at admission, have been associated with increased mortality, ICU admission, longer hospitalisation and mechanical ventilation. [32,37,38] Specifically, hyponatraemia was found to be relatively common in hospitalised COVID-19 patients and to be associated with severe illness and increased in-hospital mortality.…”
Section: In Practicementioning
confidence: 99%
“…We evaluated 1,000 patients hospitalized with COVID-19 and detected that hypernatremia was largely frequent, affecting 76.1% of individuals who died. Our results are consistent with those of other relevant investigations to date [7,[13][14][15]21].…”
Section: Discussionsupporting
confidence: 94%
“…These associations were observed in the present study, allowing a clinical characterization of COVID-19 patients in southern Brazil, reproducing the ndings of risk factors for mortality. On the other hand, hyponatremia could indicate pulmonary involvement, whereas hypernatremia is associated with prolonged LOS and the need for intensive care/mechanical ventilation, particularly when resulting from prior hyponatremia [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation